Guidelines for the use and interpretation of assays for monitoring autophagy (4th edition) - Klionsky, Daniel J. (2021)
Many researchers, especially those new to the field, need to determine which criteria are essential for demonstrating autophagy, either for the purposes of their own research, or in the capacity of a manuscript or grant review [1,2]. Acceptable standards are an important issue, particularly considering that each of us may have her/his own opinion regarding the answer. Furthermore, as science progresses and the field evolves, the answer is in part a “moving target” [3]. This can be extremely frustrating for researchers who may think they have met those criteria, only to find out that the reviewers of their work disagree. Conversely, as a reviewer, it is tiresome to raise the same objections repeatedly, wondering why researchers have not fulfilled some of the basic requirements for establishing the occurrence of an autophagic process. In addition, drugs that potentially modulate autophagy are increasingly being used in clinical trials, and screens are being carried out for new drugs that can modulate autophagy for therapeutic purposes. Clearly, it is important to determine whether these drugs are truly affecting autophagy, and which step(s) of the process/es is/are affected, based on a set of accepted criteria. To this aim, we describe here a basic set of updated guidelines that can be used by researchers to plan and interpret their experiments, by clinicians to evaluate the literature with regard to autophagy-modulating therapies, and by both authors and reviewers to justify or criticize an experimental approach. Several fundamental points must be kept in mind as we establish guidelines for the selection of appropriate methods to monitor autophagy [2]. Importantly, there are no absolute criteria for determining autophagic status that are applicable in every single biological or experimental context. This is because some assays are nsuitable, problematic or may not work at all in particular cells, tissues or organisms [1–4]. For example, autophagic responses to drugs may be different in transformed versus nontransformed cells, in confluent versus nonconfluent cells, or in cells grown with or without glucose [5]. These guidelines are likely to evolve as new methodologies are developed and current assays are superseded.